2003
DOI: 10.1081/hem-120026045
|View full text |Cite
|
Sign up to set email alerts
|

A Different Molecular Pattern of β‐Thalassemia Mutations in Northeast Brazil

Abstract: The main hereditary hemoglobin (Hb) disorders of clinical significance in Brazil are sickle cell disease and beta-thalassemia (thal). The sickle gene was introduced by the slave trade, whereas beta-thal was introduced later, due to a massive immigration (mostly by Italians) between 1870 and 1953, mainly to the southeast region of Brazil. Molecular studies performed in the southeast of the country showed a marked prevalence of the nonsense mutation at codon 39 (C --> T) (47-54%), leading to severe forms of beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
1
13
0
13
Order By: Relevance
“…Because high frequencies of some mutations of beta-thalassemia are found in the Brazilian population [23, 24], the following were investigated: CD39 (HBB: c.118C>T), IVSI-110 (HBB: c.93-21G>A), IVSI-6 (HBB: c.92 + 6T>C) and IVSI-1 (HBB: c.92 + 1G>A). Detection of these mutations was performed by allele-specific PCR, using the PS39 W (5′ GAC TCA AAG AAC CTC TG 3′) and PS39M primers (5′ GAC TCA AAG AAC CTC TA 3′) for the CD39 mutation; the TB110W (5′ GGG TGG GAA AAT AGA CC 3′) and TB110M primers (5′ GGG TGG GAA AAT AGA CT 3′) for the IVSI-110 mutation; the IVSI6W (5′ GTC TTG TAA CCT TGA TA 3′) and IVSI6M primers (5′ GTC TTG TAA CCT TGA TG 3′) for the IVSI-6 mutation and the IVSI1W (5′ GTG ACC TTG ATA CCA AC 3′) and IVSI1M primers (5′ GTG ACC TTG ATA CCA AA 3′) for IVSI-1 mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Because high frequencies of some mutations of beta-thalassemia are found in the Brazilian population [23, 24], the following were investigated: CD39 (HBB: c.118C>T), IVSI-110 (HBB: c.93-21G>A), IVSI-6 (HBB: c.92 + 6T>C) and IVSI-1 (HBB: c.92 + 1G>A). Detection of these mutations was performed by allele-specific PCR, using the PS39 W (5′ GAC TCA AAG AAC CTC TG 3′) and PS39M primers (5′ GAC TCA AAG AAC CTC TA 3′) for the CD39 mutation; the TB110W (5′ GGG TGG GAA AAT AGA CC 3′) and TB110M primers (5′ GGG TGG GAA AAT AGA CT 3′) for the IVSI-110 mutation; the IVSI6W (5′ GTC TTG TAA CCT TGA TA 3′) and IVSI6M primers (5′ GTC TTG TAA CCT TGA TG 3′) for the IVSI-6 mutation and the IVSI1W (5′ GTG ACC TTG ATA CCA AC 3′) and IVSI1M primers (5′ GTG ACC TTG ATA CCA AA 3′) for IVSI-1 mutation.…”
Section: Methodsmentioning
confidence: 99%
“…7 Thus, β + -IVS-I-6 mutation, known as the Portuguese type, is related with a more benign clinical course, whereasβ 0 39 corresponds with a more severe clinical course. 6,11,89 Certain hyperunstable structural Hb variants result in dominant thalassemic phenotypes, i.e., the presence of a single mutant allele results in clinical manifestations corresponding to intermediate thalassemia. 106 As with the SCD, heterozygotes for β-thalassemia appear to be positively selected by malaria in endemic areas, which sustains the elevated frequency of thalassemic alleles in some of these regions.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Studies in the South and Southeast of Brazil have shown that the most frequent mutations are β 0 39 (C→T) and β + IVS-I-110 (G→A) (Martins et al , 1993; Reichert et al , 2008), whereas in the Northeast, an entirely different pattern was observed, the most frequently encountered allele being β + IVS-I-6 (T→C), followed by β 0 IVS-I-1 (G→A) (Araújo et al , 2003). …”
mentioning
confidence: 99%
“…In the South and Southeast, the β 0 39 (C→T) and β + IVS-I-110 (G→A) mutations are very frequent (Martins et al , 1993; Bertuzzo et al , 1997; Fonseca et al , 1998; Reichert et al , 2008), whereas in the Northeast, the most frequent mutations are β + IVS-I-6 (T→C) and β 0 IVS-I-1 (G→A) (Araújo et al , 2003). …”
mentioning
confidence: 99%